2021
DOI: 10.1002/ccr3.4894
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal meningitis in an immunocompetent individual: A case report

Abstract: Cryptococcal meningitis (CM) is mostly seen in immune‐compromised patients and rarely occurs in immune‐competent individuals. Immunocompetent individuals with CM present with indolent neurological disease and have better clinical outcomes after treatment. However, misdiagnosis is common and these patients may suffer from serious complications with high mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…As for Nepal, in two case reports of CM in immunocompetent patients, both had apparently immunocompetent patients without any subtle immune deficits. And with the appropriate treatment as per recommended guidelines [ 1 , 8 ], both had good prognoses [ 9 , 10 ]. However, it was quite the opposite regarding our patient, who died during the course of treatment in the ICU of our center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for Nepal, in two case reports of CM in immunocompetent patients, both had apparently immunocompetent patients without any subtle immune deficits. And with the appropriate treatment as per recommended guidelines [ 1 , 8 ], both had good prognoses [ 9 , 10 ]. However, it was quite the opposite regarding our patient, who died during the course of treatment in the ICU of our center.…”
Section: Discussionmentioning
confidence: 99%
“…This could be possibly because of neurological deterioration secondary to raised intracranial pressure. There is conflicting evidence on the prognosis of CM in both immunocompetent and immunocompromised patients, with some favoring immunocompetent individuals [ 5 , 9 , 10 ]. However, mortality can also be pertinent in immunocompetent individuals because of the unavailability of investigative tools, frequent overlooking of the diagnosis and delayed presentation.…”
Section: Discussionmentioning
confidence: 99%
“…The disease cases have also been increasingly reported in healthy individuals. Acharya et al reported a case of CM in a person without any underlying disease (11).…”
Section: Discussionmentioning
confidence: 99%
“…The parameters currently utilized to assess a patient's likelihood of contracting cryptococcal meningitis are inadequate. Since fewer than 20% of patients with cryptococcal meningitis have the constellation of symptoms known as meningismus, a typical finding in meningitis, it might be difficult to make an appropriate diagnosis in the emergency department [9]. The majority of individuals with cryptococcal meningitis have at least one of the following symptoms: fever, nuchal stiffness, altered mental state, headache, or both.…”
Section: Discussionmentioning
confidence: 99%